2012
DOI: 10.4103/2249-4847.96755
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: A study of incidence and risk factors in NICU of Al-Minya University Hospital in Egypt

Abstract: Background:Retinopathy of prematurity (ROP) is a serious complication of prematurity treatment and can lead to blindness unless recognized and treated early.Objective:To estimate the incidence of ROP in preterm infants in our NICU, to identify the risk factors which predispose to ROP, and to assess the outcome of these cases.Materials and Methods:ROP prospective screening survey was performed enrolling all prematures admitted to the NICU from January 2009 to December 2010, with a gestational age of 32 weeks or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
5
14
1
Order By: Relevance
“…The inclusion criteria for premature infants varied considerably: the GA criteria ranged from <28 weeks to <37 weeks, and only 12 studies provided the specific BW range. Most included studies reported the multivariable-adjusted OR and corresponding 95% CI, although one study provided only univariate analysis outcomes 17. There were eight prospective cohort studies, seven retrospective cohort studies and one nested case-control study, which also came from an institutional retrospective cohort.…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion criteria for premature infants varied considerably: the GA criteria ranged from <28 weeks to <37 weeks, and only 12 studies provided the specific BW range. Most included studies reported the multivariable-adjusted OR and corresponding 95% CI, although one study provided only univariate analysis outcomes 17. There were eight prospective cohort studies, seven retrospective cohort studies and one nested case-control study, which also came from an institutional retrospective cohort.…”
Section: Resultsmentioning
confidence: 99%
“…[58,60] Thus, it is important to adjust for the influence of oxygen and mechanical ventilation on the relationship of sepsis and ROP. However, of the 34 studies included, only 7 studies [22,26,33,35,36,40,44] had concurrently adjusted for this 2 factors. In addition, although there are 14 studies which adjusted the confounder of oxygen use, the bias may still exist because it is difficult to adjust appropriately for oxygenation to normalizing the oxygenation among studies.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ROP in our study is 25%, in concordance with various studies, in which the reported incidence ranges from 19% to 26% among the low-birth-weight babies. [91011]…”
Section: Discussionmentioning
confidence: 99%